Gender variations in HIV related stigma among Indian adults - Barman, Paramita (International Journal Of Community Medicine And Public Health, 2022)
Background: Human immunodeficiency virus (HIV) is a global public health problem. Social stigma and discrimination around HIV can be a strong deterrent to seeking healthcare and deny people living with HIV (PLHIV) a life of dignity. Further, gender has a role in determining utilization of available healthcare service. Although research has been conducted on gender differences in experience of stigma among PLHIV, there remains a gap with respect to cross gender study of the determinants of HIV related stigma in the context of India which has the third highest burden of HIV globally. This serves as the motivation of the current study. Methods: The study uses unit level data on adult men and women from the NFHS-4 (2015-16) survey. Logistic regression has been used for analysis of data. Results: Higher percentage of adult women than men nurture HIV related stigma at all India level. Multivariate analysis reveals that for both genders, stigma falls significantly with higher educational attainment but increases with higher economic class. Differences in drivers of stigma across men and women remain with respect to religion, age, employment and marital status. Conclusions: Awareness raising and stigma reducing interventions designed in view of gender specific requirements are called for to curb social discrimination against PLHIV and ensure better quality of life for them.